PLACE OF FREEDOM IN THE HIERARCHY MORAL VALUES - Желуденко, М.О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article is devoted to the analysis of different approaches to the definition of the notion of freedom and the place of freedom in the hierarchy of moral values. Freedom is considered as one of the highest values which forms the basis of the upbringing of moral person, that corresponds to the main tasks of modern education.